Oral-dental hygiene and oral microorganisms in children with and without congenital heart disease - Erniwaty P Panggabean; Lily Irsa; Rosihan Anwar; Munar Lubis; Rusdidjas Rusdidjas; Syahril Pasaribu (Paediatrica Indonesiana, 2005)
Objective This study was done to compare the dental and oralhygiene status of children with and without congenital heart dis-ease (CHD) by investigating oral microorganisms and dental andoral hygiene indices.Methods A cross-sectional study was done on children aged 2 to15 years from April 2002 to December 2003 at the Department ofChild Health, Haji Adam Malik Hospital, Medan. There were twosubject groups, the first consisting of children with CHD and thesecond of those without. The dental and oral hygiene status wasdetermined by determining caries index and oral hygiene index.Swabs from the subjects’ upper first molars were taken and cul-tured to determine the types of microorganisms present. Data wereanalyzed using the chi-square test, Fisher’s exact test, and t-test.Results There was a significant difference in mean oral hygieneindex between children with (mean 2.75; SD 1.85) and without(mean 1.45; SD 0.78) CHD (P<0.001). Positive bacterial cultureswere more frequent in children with CHD than in those without.The proportion of normal anaerobes was significantly higher in chil-dren with CHD (P=0.038). Such a significant difference was notfound for normal aerobes, pathogenic aerobes, and pathogenicanaerobes. In children with CHD, there was no significant asso-ciation between mean caries index and oral hygiene index withculture results. In those without CHD, a significant association wasfound between the caries index components of decayed tooth in-dex (P=0.003) and DMF-T (P=0.022) with culture results.Conclusions Oral-dental hygiene in children with CHD is poorrelative to that in children without CHD. Microorganism growth ap-pears more likely in children with CHD than in those without